Natureza, terra e trabalho na educação do MST: o caso do assentamento Congonhas Abelardo Luz SC - Paim, Robson Olivino (2011)
The struggle for land is not an end in the conquest of a property. The terms of productivity, social cohesion, environmental quality and education are key variables for the quality assurance of a social process of agrarian reform. This study in the Settlement Congonhas-Abelardo Luz / SC seeks to assess the extent to which the educational processes of Middle Level Integrated Course in Natural Sciences - Agroecology Technician developed in High School Paulo Freire contributes to the development and enhancement of agroecology work in communities and local knowledge of the settlement. We chose a case study with a qualitative approach, with the instruments of data collection semi-structured interviews, questionnaires, and documentary and bibliographic sources. Regarding the school, it was observed that this has, in low intensity, the conditions necessary for the potential implementation of agroecological production strategies through the creation of collective consciousness. On the other hand, the objective and subjective conditions necessary for agroecology in the properties are still incipient, with no knowledge about the fundamentals of agroecology and having the need for immediate productive results the main argument in agroecology to develop properties. It is concluded that the settlement in question has characteristics of light training of human resources for the implementation of agroecological production systems. It is suggested further development of environmental education activities in order to contribute to the formation of a new vision about agroecology and, later, the group can claim ownership of the settlement of agroecological technologies and access to agricultural policies, markets, incentives financial and political stability of agroecosystems.